2023
DOI: 10.1128/spectrum.00364-23
|View full text |Cite
|
Sign up to set email alerts
|

Lysis Cassette-Mediated Exoprotein Release in Yersinia entomophaga Is Controlled by a PhoB-Like Regulator

Abstract: While theoretical models exist, there is not yet any empirical data that links ALC phage-like lysis cassettes with the release of large macro-molecular toxin complexes, such as Yen-Tc in Gram-negative bacteria. In this study, we demonstrate that the novel Y. entomophaga RoeA activates the production of exoproteins (including Yen-Tc) and the ALC at the transcriptional level.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…This is consistent with a report from Y. enterocolitica , where a phage-related holin/endolysin pair was suggested to be important for the release of its insecticidal toxin complex 29 . A similar LC has been identified by a transposon screen in Y. entomophaga WT, but the LC was not encoded in the vicinity of the YenTc gene cluster 25 , 30 . This LC encodes a holin ( holA ), an endolysin ( pepB ) and two spanin ( rz , rz1 ) genes (Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…This is consistent with a report from Y. enterocolitica , where a phage-related holin/endolysin pair was suggested to be important for the release of its insecticidal toxin complex 29 . A similar LC has been identified by a transposon screen in Y. entomophaga WT, but the LC was not encoded in the vicinity of the YenTc gene cluster 25 , 30 . This LC encodes a holin ( holA ), an endolysin ( pepB ) and two spanin ( rz , rz1 ) genes (Fig.…”
Section: Resultssupporting
confidence: 54%
“…b , Schematic of the LC gene cluster in Y. entomophaga , which comprises a holin, an endolysin and two overlapping spanin open reading frames (gene names are indicated). This gene cluster has been previously identified, being involved in general exoproteome release 30 . c , Western blot analysis against YenA1 and RecA (loading control) of Y. entomophaga WT and ΔLC mutants showed that both strains expressed YenA1, but release into the supernatant (sup.)…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1b ). Importantly, another group independently verified the importance of YenLC and RoeA for lytic protein release and YenTc production during review of this study 44 . To avoid potential confusion, we have adopted YenLC component nomenclature from that study.…”
Section: Resultsmentioning
confidence: 60%
“…The data presented here corroborates that the sef-tc island likely existed before becoming associated with the STAMP backbone. that Yersinia Holin (lysis cassette), which is associated with secreting Tcs, is only expressed in a subset of the population (<10%) (Schoof et al, 2023). Through TEM, it was established that only ~10% of WT S. entomophila A1MO2 cells were observed to be fimbriated.…”
Section: Expression and Deletion Of Sef Operon Confirms Fimbriae Prod...mentioning
confidence: 99%